Striking appropriate balance between metadata retention and right to privacy according to the Article 7 of the CFREU - Konopko, Andrii (My University, 2019)
Metadata retention based on the modern technology capabilities is proven to be an effective tool for the investigation and prevention of crimes. However, this governmental tool if not properly limited can lead to mass surveillance and imposes a grave intrusion into privacy. European metadata retention regime established by the Data Retention Directive (2006-2014) fell with the decision of the CJEU in Digital Rights Ireland case. The struggle with understanding how metadata retention can be applied on the national level continues even after the following Tele2&Watson case.⁣ ⁣ Presented master thesis is an effort to analyze what was wrong with Data Retention Directive and a springboard to understanding how to build a national metadata retention framework to be in compliance with the European Union law. The research is based on analysis of privacy and metadata retention as two contradicting issues. The researcher pays thorough attention to Article 7 of the Charter of Fundamental Rights and 2 landmark decisions of the CJEU: Digital Rights Ireland and Tele2&Watson.⁣ ⁣ Special emphasis in the work is put on analyzing the conditions which allow limiting the right to privacy by means of metadata retention: objective of general interest, provision by law, respect to the essence of the right to privacy and proportionality of the intrusion. The thesis also focuses on ‘what is strictly necessary’ limitations with regard to amount of people concerned, categories of data, means of communication affected and time period of retention. The outcome of the research confirms that it is highly possible to build up a national metadata retention law even with the imposed by CJEU limitations.
Keywords: privacy, data protection, metadata retention, proportionality, Data Retention Directive, Digital Rights Ireland, Tele2&Watson, CFREU, right to privacy, surveillance